2007
DOI: 10.1159/000111027
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Surgically Induced Remission of Crohn’s Disease

Abstract: At 1 year after a first resection, up to 80% of patients show an endoscopic recurrence, 10–20% have clinical relapse, and 5% have surgical recurrence. Smoking is one of the most important risk factors for postoperative recurrence. Preoperative disease activity and the severity of endoscopic lesions in the neoterminal ileum within the first postoperative year are predictors of symptomatic recurrence. Mesalazine is generally the first-line treatment used in the postoperative setting but still provokes considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 95 publications
(60 reference statements)
1
12
0
3
Order By: Relevance
“…23,47 The effectiveness of azathioprine and 6-mercaptopurine for the prevention of POR was recently analyzed. 15,98,99 In a prospective randomized study involving 142 patients divided into 2 groups (Group A1: patients treated with azathioprine 2 mg/kg/die; Group A2: patients treated with mesalamine 3 g/day for 24 months) Ardizzone et al found that the risk of recurrences was comparable in both groups. Although we cannot observe any significant difference in the percentage of recurrence for the two groups, analyzing the results based on other parameters, azathioprine is more effective than mesalamine in preventing clinical recurrences in patients with previous bowel resection.…”
Section: Immunosuppressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,47 The effectiveness of azathioprine and 6-mercaptopurine for the prevention of POR was recently analyzed. 15,98,99 In a prospective randomized study involving 142 patients divided into 2 groups (Group A1: patients treated with azathioprine 2 mg/kg/die; Group A2: patients treated with mesalamine 3 g/day for 24 months) Ardizzone et al found that the risk of recurrences was comparable in both groups. Although we cannot observe any significant difference in the percentage of recurrence for the two groups, analyzing the results based on other parameters, azathioprine is more effective than mesalamine in preventing clinical recurrences in patients with previous bowel resection.…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…15,43,98,107 Faecal bacteria in fact have been implicated in the genesis of recurrence in patients operated for CD. 108 The role of metronidazole was investigated in a study including 60 patients, divided randomly into two groups: group A e patients treated with metronidazole for 3 months, starting from the first week after ileal resection, group B e patients treated with placebo.…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main indications for endoscopic dilatation are short, isolated, and non-fistulizing strictures that are within the reach of a standard colonoscope, with many amenable strictures localized at the site of the ileocecal anastomosis after ileocecal resection [107]. An immediate technical success of endoscopic dilation, a stricture length B4-cm, and the absence of ulcers in the stricture are positively associated with successful dilatation [87,108,109].…”
Section: Endoscopic Dilationmentioning
confidence: 99%
“…The best treatment for the prevention of post-operative CD recurrence is yet to be established. The efficacy of mesalazine in preventing post-operative recurrence is only slightly superior to the efficacy of a placebo [8,9,10], and the efficacy of thiopurines, such as azathioprine and mercaptopurine (MP), remains a subject of debate [11,12,13,14,15]. A meta-analysis showed that purine analogues were more effective than placebo in preventing endoscopic recurrence (defined by Rutgeerts score [Rs] ≥i2) but not for preventing very severe endoscopic recurrence (Rs = i3-i4).…”
Section: Introductionmentioning
confidence: 99%